Arabidopsis CKI1 mediated two-component signaling in the specification of female gametophyte. (3rd October 2018) - Liu, Z.; Yuan, L.; Sundaresan, V.; Yu, X.
ABSTRACT: Cytokinin independent 1 (CKI1) is a histidine kinase involved in the two-component signaling pathway and acts as a master regulator of central cell specification via CKI1-mediated two-component signaling. In this study, the dynamic distribution of two-component system (TCS) signals was primarily investigated during Arabidopsis embryo sac development. TCS signals were stably detected in female gametophytes cells from the megaspore stage all through to the mature embryo sac stage. CKI1 acts as the primary activator of the TCS signaling pathway in embryo sacs. Accordingly, focusing on CKI1, two alternate models are proposed for female gametophyte cell fate specification. In the first model, CKI1 co-determines the central cell fate in combination with a hypothetical X factor at the micropylar pole, and in the alternate model, CKI1 alone determines the central cell fate.